2023
DOI: 10.1038/s41893-023-01063-2
|View full text |Cite|
|
Sign up to set email alerts
|

Prioritizing India’s landscapes for biodiversity, ecosystem services and human well-being

Abstract: Biodiversity conservation and human well-being are tightly interlinked. Yet, mismatches in the scale at which these two priority issues are planned and implemented have exacerbated biodiversity loss, erosion of ecosystem services and declining human quality of life. India houses the second largest human population on the planet, while < 5% of the country's land area is effectively protected for conservation. This warrants landscape-level conservation planning through a judicious mix of land-sharing and land-sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…For instance, Target 3 calls for the protection of areas of particular importance for biodiversity and ecosystem functions and services . Yet, a recent study showed that the current PA network in India includes only 15% of the top priority conservation sites that represent critical natural habitats, provide crucial ecosystem services, and contain a diversity of threatened species (Srivathsa et al., 2023). The network also does not represent well‐connected…systems and are often not integrated into wider landscapes, seascapes and the ocean , as Target 3 suggests.…”
Section: What Does Target 3 Mean For India?mentioning
confidence: 99%
“…For instance, Target 3 calls for the protection of areas of particular importance for biodiversity and ecosystem functions and services . Yet, a recent study showed that the current PA network in India includes only 15% of the top priority conservation sites that represent critical natural habitats, provide crucial ecosystem services, and contain a diversity of threatened species (Srivathsa et al., 2023). The network also does not represent well‐connected…systems and are often not integrated into wider landscapes, seascapes and the ocean , as Target 3 suggests.…”
Section: What Does Target 3 Mean For India?mentioning
confidence: 99%
“…The same is true for trade-offs among other services. In BTH and other urban agglomerations, fully understanding the relationship between ESs and identifying the most reasonable priority regions to improve ESs by allocating reasonable target weights can ensure that the efficient use of resources and the improvement of landscape sustainability complement each other (Srivathsa et al 2023).…”
Section: Trade-off Curves For Es Supply-demand Optimization In Urban-...mentioning
confidence: 99%
“…In the realm of world biodiversity, the Indian Subcontinent is recognized for its exceptional species diversity and ecosystem services [ 1 ]. Among the global spectrum of 75 bird families, this region boasts an impressive record with 48 families within its extent, thereby making a significant contribution of over 13 % to the overall global bird population [ [2] , [3] , [4] ].…”
Section: Introductionmentioning
confidence: 99%